1987
DOI: 10.1016/0022-0728(87)80248-6
|View full text |Cite
|
Sign up to set email alerts
|

Redox potential and electrocatalysis of O2 reduction on transition metal chelates

Abstract: The redox potentials of iron phthalocyanine (FePc), cobalt phthalocyanine (CoPc) and cobalt tetraaxaammlene (CoTAA), irreversibly adsorbed on pyrolytic graphite, were investigated as a function of the pH by cyclic voltammetry. The reduction of oxygen was studied under the same conditions with the rotating disc electrode technique. At high pH, where the reduction to H,Or on the cobalt-containing chelates is more reversible, the value of the redox potential is less important. At low pH, where this reduction is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 13 publications
2
51
0
1
Order By: Relevance
“…The electrochemical behavior of these films is to a large extent detected by the physical properties of the film, such as the condition and the permeability towards O 2 . These authors also observed that at high pH, the reduction to H 2 O 2 on the Co-containing chelates is more reversible, independent of the redox potential; at low pH, the reduction is irreversible and there is a clear correlation between the redox potential of the central metal ion and the O 2 -reduction behavior [128].…”
Section: Co-and Fe-based Phthalocyanines (Pc)mentioning
confidence: 92%
“…The electrochemical behavior of these films is to a large extent detected by the physical properties of the film, such as the condition and the permeability towards O 2 . These authors also observed that at high pH, the reduction to H 2 O 2 on the Co-containing chelates is more reversible, independent of the redox potential; at low pH, the reduction is irreversible and there is a clear correlation between the redox potential of the central metal ion and the O 2 -reduction behavior [128].…”
Section: Co-and Fe-based Phthalocyanines (Pc)mentioning
confidence: 92%
“…Iron(II) phthalocyanine (FePc) complexes are important for the electrocatalytic reduction of molecular oxygen since such reduction reactions occur at a low potential, yielding water as the main product [8,30]. Few reports exist on the use of nanosized FePc (nanoFePc) for electrocatalytic detection [31 -33], however, until now, there has not been any report on the use of nanoFePc or its CNTs hybrids (nanoFePc-CNTs) for electrocatalytic reduction of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Various electrodes such as those based on carbon paste [6], highly oriented pyrolytic graphite [7,8], silver [9,10], palladium [11], glassy carbon [12,13], edge plane pyrolytic graphite [14], basal plane pyrolytic graphite [15], Platinum [16] and boron-doped diamond [17] have been used for these studies. The unique and useful electrical and mechanical properties exhibited by carbon nanotubes (CNTs) have made it a promising candidate in various applications in nanoscale science and technology.…”
Section: Introductionmentioning
confidence: 99%
“…Metallophthalocyanines (MPcs) have attracted considerable interest as the OR catalyst, due to their rich redox behavior, ability to involve various metals in the central cavity, easy modification by substituting the ring, chemical stability and high methanol tolerance [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The central metal ion in a MPc seemed to play a decisive role in the OR mechanism, because of its ability to bind dioxygen molecule and thus to form suitable intermediates [1,8,9,13].…”
Section: Introductionmentioning
confidence: 99%